A Case of Dissociative Fugue and General Amnesia with an 11-Year Follow-Up. Issue 1 (1st January 2015) - Helmes, Edward; Brown, Julie-May; Elliott, Linda
Abstract : Dissociative fugue refers to loss of personal identity, often with the associated loss of memories of events (general amnesia). Here we report on the psychological assessment of a 54-year-old woman with loss of identity and memories of 33 years of her life attributed to dissociative fugue, along with a follow-up 11 years later. Significant levels of personal injury and stress preceded the onset of the amnesia. A detailed neuropsychological assessment was completed at a university psychology clinic, with a follow-up assessment there about 11 years later with an intent to determine whether changes in her cognitive status were associated with better recall of her life and with her emotional state. Psychomotor slowing and low scores on measures of attention and both verbal and visual memory were present initially, along with significant psychological distress associated with the diagnosis of posttraumatic stress disorder. Although memories of her life had not returned by follow-up, distress had abated and memory test scores had improved. The passage of time and a better emotional state did not lead to recovery of lost memories. Contrary to expectations, performance on tests of executive functions was good on both occasions. Multiple stressful events are attributed as having a role in maintaining the loss of memories.